Design Strategies Toward Zinc Anodes with High Utilization Rate for Practical Aqueous Zinc-Ion Batteries - Meng, Yahan; Qi, Jintao; Li, Apeng; Li, Xiang; Xu, Ze; Ding, Kunjie; Wang, Mingming; Chen, Ying Ian; Huang, Shaoming (Nano-Micro Letters, 2026)
Aqueous zinc-ion batteries (AZIBs) have emerged as promising candidates for large-scale energy storage systems due to their high safety, low cost, and environmental friendliness. However, the zinc (Zn) anode faces a series of side reactions, including hydrogen evolution, dendrite growth, corrosion, and passivation, leading to irreversible loss of active Zn material and a significant reduction of cycling stability of the Zn anode. To mitigate the impact of these issues, an excess of Zn anode is commonly employed to ensure a continuous supply of Zn during long-term operation. However, the use of excess Zn results in a practical energy density of AZIBs that is far below the requirements for commercialization. Improving Zn anode utilization rate (ZUR) and optimizing the negative/positive electrode capacity ratio (N/P) are effective pathways to achieve high energy density. This review systematically summarizes the challenges associated with Zn anodes with high ZUR and provides a detailed discussion on modification strategies to improve the ZUR from three aspects: the anode, electrolyte, and separator. Finally, we look ahead to the future development directions and prospects of Zn anodes with high ZUR and AZIBs with high energy density. With ongoing technological advancements and continuous innovation, we believe AZIBs have the potential to overcome current bottlenecks and contribute to the global development of sustainable energy systems. Highlights: 1 ZUR as Key Metric: High zinc utilization rate (ZUR) is identified as the decisive factor for bridging the gap between theoretical and practical energy densities in aqueous zinc-ion batteries (AZIBs). 2 Tri-part Modification: The review systematically evaluates current advancements in stabilizing zinc anodes under high ZUR by engineering the anode structure, electrolyte composition, and separator functions. 3 Commercial Roadmap: Future perspectives emphasize standardized testing—including low N/P ratios and lean electrolytes, alongside AI-driven material screening to accelerate AZIB industrialization.